The Blind Spots of Neoclassical Economics in the Political Economy of 21st-Century Cocaine - Vélez, Álvaro (2025)
The text raises the existence of conceptual, empirical and disciplinary limitations in neoclassical economics that hinder the understanding of the complexities related to the cocaine economy in the Andean countries. It is argued that the Political Economy of Cocaine alone cannot address all the dimensions and processes linked to this phenomenon. To address this issue more fully, it is suggested that the interconnections between the Political Economy of Cocaine, Political Ecology PE and Ecological Economics EE be explored, especially with regard to the environmental consequences of coca leaf cultivation and cocaine trade. The need to consider different approaches and disciplines for a more comprehensive understanding is raised. In addition, it proposes the development of a “New Political Economy” that goes beyond the traditional conceptual framework centered on “drug trafficking”. This implies the recalibration and reformulation of existing concepts for a more precise understanding of the Political Economy of Cocaine and its implications for the Andean countries and Latin America.